Improving the Efficiency of Healthcare Services in Medical Practices Through a Web-Based Data Management System - Asep Ririh Riswaya; Heri Wahyudi (Majalah Bisnis & IPTEK, 2025)
The patient data management system in healthcare services currently faces serious challenges regarding data security and availability. Many system users can access patient information without proper authorization, which increases the risk of sensitive data leaks and misuse of information. Doctors have not fully implemented comprehensive security protocols to maintain the confidentiality and integrity of data, further worsened by the lack of authentication mechanisms and staff education on digital security. Additionally, disruptions to the system can lead to downtime, reducing data availability and directly impacting healthcare operations. This research aims to enhance the efficiency of healthcare services in medical practices by developing a web-based data management system that presents accurate and up-to-date information. The system development follows the Waterfall method and incorporates One Time Password (OTP) security features to ensure controlled and secure data access. The implementation of this system is expected to improve the quality of healthcare services by speeding up service processes while safeguarding patient information.